PELATIHAN PEMANFAATAN APLIKASI MANAJEMEN REFERENSI ZOTERO DALAM MENINGKATKAN KUALITAS PEMAHAMAN GURU-GURU SD DALAM MEMBUAT KARYA TULIS ILMIAH - Febby Fajar Nugraha; Dede Awaludin; Galih Dani Septiyan Rahayu (Abdimas Siliwangi, 2021)
In today's era, teachers are required to have more abilities related to the use of technology as a tool in writing scientific papers. This is because there are still a lot of teachers who are still confused in finding reference applications in writing scientific papers. One application that is used to make it easier for teachers to write scientific papers, especially in managing references is the Zotero application. The purpose of this program of activity is to provide training and guidance for teachers who are required to write scientific papers as demand for self-quality improvement and learning in order to increase class in teaching positions. The method used in this Community Service is through the workshop approach method, lectures, questions and answers, and guidance on the use of the application, with the guidance process is expected to provide opportunities for teachers according to the training theme. This community service activity can provide direct benefits to partners in increasing understanding and skills related to reference management applications in the preparation of scientific papers in the form of CAR, indicators of the success of community service activities marked by the enthusiasm of the teachers in participating in training activities.